Environmental and social valuation of shipping emissions on four ports of Portugal - Rafael A.O. Nunes (2019)
Maritime sector is expected to continue growing significantly in line with world trade, however its impacts on environmental, social and human health are not yet fully known. Thus, this study aimed to estimate the external costs of in-port shipping emissions (NOx, SO2, CO2, VOCs and PM2.5) and accomplish a comprehensive eco-efficiency evaluation of four ports in Portugal (Leixoes, Setubal, Sines and Viana do Castelo) during 2013. External costs were based on the external cost factors from BeTa, CAFE and NEEDS projects and from Song (2014). Eco-efficiency evaluation was based on environmental, social and economic criteria. Results showed higher externalities for Sines and Setubal (2.0E +02 million (sic)), followed by Leixoes (1.8E + 02 million (sic)), and Viana do Castelo (6.3 million (sic)). NOx, SO2, and PM2.5 were the pollutants with the highest externalities. Sines port showed the best overall eco-efficiency. Although Setubal port showed higher performance than Viana do Castelo port based on the economic data, when social and environmental aspects were considered the results changed. This shows the importance of performing a more comprehensive analysis using social and environmental indicators. The combination of all these indicators is highly important to support the implementation of policies for the abatement of shipping in-port emissions.